Non-nicotine constituents in cigarette smoke extract enhance nicotine addiction through monoamine oxidase A inhibition - Liu, Guanglin; Wang, Ruiyan; Chen, Huan; Wu, Ping; Fu, Yaning; Li, Kaixin; Liu, Mingda; Shi, Zhihao; Zhang, Yuan; Su, Yue; Song, Lingxiao; Hou, Hongwei; et al. (Frontiers in Neuroscience, 2022)
Tobacco addiction has been largely attributed to nicotine, a component in tobacco leaves and smoke. However, extensive evidence suggests that some non-nicotine components of smoke should not be overlooked in tobacco addiction. Yet, their individual effect and synergistic effect on nicotine addiction remain poorly understood. The study herein investigated the role of non-nicotine constituents in promoting the effects of nicotine and their independent addictive potential. Denicotinized cigarettes were prepared by chemical extracting cut tobacco, and the cigarette smoke extracts (CSE, used as a proxy for non-nicotine ingredients) were obtained by machine-smoking first and DMSO extraction. The compositions of harmful components, nicotine, and other minor alkaloids in both cut tobacco and the CSE of experimental denicotinized cigarettes were then examined by the GC-MS, and compared with 3R4F reference cigarettes. The CSE addiction potential individually and in synergy with nicotine was determined by conditioned place preference (CPP), dopamine (DA) level detection, the open field test (OFT), and the elevated plus maze (EPM). Finally, the potential enhancement mechanism of non-nicotinic constituents was investigated by nicotine metabolism and monoamine oxidase A (MAOA) activity inhibition in the striatum of mice and human recombinant MAOA. The smoke nicotine content under ISO machine-smoking conditions of the prepared experimental denicotinized cigarettes reduced smoke nicotine content by 95.1% and retained most minor alkaloids, relative to the 3R4F reference cigarettes. It was found that non-nicotine constituents in concert with nicotine further increased acute locomotor activities, as well as anxiogenic effects after withdrawal, especially the DA levels and CPP scores (time spent in the drug-paired boxes), which is suggestive of increased addiction potential; there were no differences in these metrics of non-nicotine constituents compared to the saline control. Non-nicotine constituents alone didn’t show addiction potential in CPP or striatum DA levels in mice. However, non-nicotine constituents in concert with nicotine further increased the addiction potential. Furthermore, non-nicotine constituents may enhance nicotine’s addictive potential by inhibiting striatum MAOA activity rather than affecting nicotine metabolism or total striatum DA content in mice. These findings expand our knowledge of the effect on smoking addiction of non-nicotine constituents found in tobacco products.